PERANCANGAN PROMOSI EVENT TEATER BONEKA SEBAGAI KAMPANYE TOLERANSI BERAGAMA - SASKIA PUTRI AGUSTINE; NINA NURVIANA; MIKI TJANDRA (Serat Rupa: Journal of Design, 2016)
Indonesia acknowledges the existence of six religions. However, this diversification is often met with some intolerance by the religion of majority in different regions, one of the examples of which is West Java. For five consecutive years (2009-2014), West Java is on the first rank of religion intolerance. Thus, the knowledge of tolerance towards the other religions needs to be implemented since the early age, particularly those coming out of modest families. The purpose of this design is to grow the essence of religion tolerance for the Moslems as the majority so that they can get to know the other religions in Indonesia via stories narrated through displays. The purpose is to make people willing to accept divergence of religion and to eventually make generations able to cope up with and respect religions with distinct concepts with one another. The approach implemented is to retell fairy tales with puppets as the representation and media. The puppets embody six different characters metaphorically symbolizing six different religions in Indonesia. This activity is promoted by making use of motion graphic and booklets as well as gimmick as complements.Keywords: campaign; children of early age; Islam; puppet show; religion tolerance